Less : a novel - Greer, Andrew Sean (New York : Back Bay Books/Little, Brown and Company, 2018)
Receiving an invitation to his ex-boyfriend's wedding, Arthur, a failed novelist on the eve of his fiftieth birthday, embarks on an international journey that finds him falling in love, risking his life, reinventing himself, and making connections with the past.
Originally published in hardcover by Little, Brown and Company in 2017.
Pultizer Prize for Fiction, 2018
Keywords: Authors -- Fiction; Gay men -- Fiction; Friendship -- Fiction; Americans -- Foreign countries -- Fiction; Time -- Psychological aspects -- Fiction; Voyages and travels -- Fiction; Humorous fiction